Intracerebral hemorrhage and thrombin-induced alterations in cerebral microvessel matrix. Issue 9 (September 2022) - Gu, Yu-Huan; Hawkins, Brian T; Izawa, Yoshikane; Yoshikawa, Yoji; Koziol, James A; del Zoppo, Gregory J
Four phase III clinical trials of oral direct factor Xa or thrombin inhibitors demonstrated significantly lower intracranial hemorrhage compared to warfarin in patients with nonvalvular-atrial fibrillation. This is counter-intuitive to the principle that inhibiting thrombosis should increase hemorrhagic risk. We tested the novel hypothesis that anti-thrombin activity decreases the risk of intracerebral hemorrhage by directly inhibiting thrombin-mediated degradation of cerebral microvessel basal lamina matrix, responsible for preventing hemorrhage. Collagen IV, laminin, and perlecan each contain one or more copies of the unique α-thrombin cleavage site consensus sequence. In blinded controlled experiments, α-thrombin significantly degraded each matrix protein in vitro and in vivo in a concentration-dependent fashion. In vivo stereotaxic injection of α-thrombin significantly increased permeability, local IgG extravasation, and hemoglobin (Hgb) deposition together with microvessel matrix degradation in a mouse model. In all formats the direct anti-thrombin dabigatran completely inhibited matrix degradation by α-thrombin. Fourteen-day oral exposure to dabigatran etexilate-containing chow completely inhibited matrix degradation, the permeability to large molecules, and cerebral hemorrhage associated with α-thrombin. These experiments demonstrate that thrombin can degrade microvessel matrix, leading to hemorrhage, and that inhibition of microvessel matrix degradation by α-thrombin decreases cerebral hemorrhage. Implications for focal ischemia and other conditions are discussed.